Interfaith Marriage from the Perspective of Rationality: Theocentrism in Islamic Law and Anthropocentrism in Human Rights Law - Salam, Nor; Purnomo, Agus; Saifullah, Saifullah; Ahmad, Sirojuddin (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
This article stems from a theoretical debate concerning interfaith marriage as formulated within Islamic and human rights laws. While Islamic law tends to prohibit interfaith marriage, human rights instruments view it as an individual's right and freedom. Therefore, this research aims to scrutinise the argumentative basis of Islamic law and human rights law regarding interfaith marriage. To address this focal issue, this study employed a literature research model reliant on content analysis, bearing the result concluding that the disparity in formulations between Islamic law and human rights law regarding the legality of interfaith marriage is due to their differing argumentative bases: Islamic law is rooted in theocentrism, whereas human rights law is rooted in anthropocentrism. However, by examining the opinions of contemporary thinkers regarding maqashid sharia, there appears to be a paradigm shift in theocentrism of Islamic law so that in the context of interfaith marriage, both Islamic law and human rights can justify it as part of a person's human rights.